Integration Of Ai Tools In Healthcare, Employee Perceptions, Productivity And Workload Management - Rameez Ahmad , Khawaja Hisham-Ul-Hassan, Muhammad Ammar Masood Cheema, Mehreen Naz, Qaiser Iqbal (Migration Letters, 2024)
This qualitative study explores how healthcare professionals in tertiary care hospitals of Gujranwala perceive AI integration in their work routines and its impact on productivity and workload management. Interviews with 30 participants from diverse roles, including doctors, nurses, administrative staff, and other health workers, were conducted using a semi-structured approach. Thematic analysis revealed key insights into AI’s perceived usefulness, its effects on productivity, workload management, and job satisfaction. While AI shows potential for efficiency gains, concerns about role changes, security, and the need for ongoing training persist. These findings offer a crucial starting point to assess AI perceptions and support healthcare professionals’ well-being in a technological society.